A new chiral Fe(iii)–salen grafted mesoporous catalyst for enantioselective asymmetric ring opening of racemic epoxides at room temperature under solvent-free conditions. Issue 9 (17th December 2015) - Roy, Susmita; Bhanja, Piyali; Safikul Islam, Sk.; Bhaumik, Asim; Manirul Islam, Sk.
Abstract : A new heterogeneous chiral Fe(iii )–salen grafted mesoporous catalyst has been synthesized for the enantioselective (ee > 99%) ARO reaction of racemic epoxides with aromatic amine under solvent-free conditions. Abstract : We have designed a new mesoporous SBA-15 supported chiral Fe(iii )–salen material (Fe@SBSAL) having high BET surface area and porosity. The material showed excellent catalytic efficiency in regio- and enantioselective (ee > 99%) asymmetric ring opening (ARO) of racemic meso - and terminal-epoxides with various anilines at room temperature under solvent-free conditions within 1–3 h reaction time.